Development of micro-nuclear generators for autonomous systems - Ayodele, Olukayode Lawrence (Cape Peninsula University of Technology, 2022)
As concerns over clean power generation grow, it is a relief that a considerable quantity of underutilized waste heat could be used to provide clean power for hundreds of years. The increased interest in space research, satellite operations, structural health monitoring, and terrestrial monitoring in hostile and inaccessible zones places a high demand for energy sources for autonomous systems. In the same vein, there is also a growing interest in reliable and low-cost power sources for utility applications. Conventional electrochemical batteries that could be used for utility-scale energy storage are plagued by low energy storage density, short life, disposal of unwanted batteries, and related undesired maintenance requirements of recharging or replacement, which endangers the environment. Wind, fuel cell, and solar energy sources being exploited to mitigate the adverse effect of environmental threats posed by batteries and fossil fuels are costly to acquire and maintain. The availability of energy sources derived from waste heat from radioactive decay for domestic appliances and industrial equipment will also help alleviate the effects of climate change, which continues to threaten the environment due to fossil fuel energy-based sources that emit harmful carbon monoxide into the atmosphere. A combination of energy from waste heat, harvested via thermoelectricity and existing battery technology to produce a hybrid energy source will guarantee secured energy for a long period. Based on the Seebeck effect, thermoelectric energy generation may considerably contribute to sustainable energy development and meet the growing demand for power in utility applications. Mathematical modeling of the energy from waste heat, existing battery technologies, and a hybrid energy source are considered, and their performances are established using the MATLAB/Simulink environment. Results confirmed the comparative advantage of hybrid energy source over and above the respective electrochemical batteries and waste heat energy source in terms of effectiveness and performance efficiency. Since batteries are required to operate in a constantly changing environment, the effects of temperatures on batteries were investigated. The results show that the performances of batteries decrease with a decrease in ambient temperature and that the higher the maximum operating capacity, the higher the internal temperature of the battery.
Thesis (DEng (Mechanical Engineering))--Cape Peninsula University of Technology, 2022
Keywords: Electric batteries; Energy storage; Storage batteries; Hybrid power systems; Waste products as fuel; Renewable energy sources